Development of the system of sources of Kazakh law - Akhmetova, N.S.; Starozhilova, N.P. (Bulletin of the Karaganda University “Law Series”, 2020)
The aim of the study is to analyze the sources of law of the Republic of Kazakhstan as an independent systemic phenomenon, formulate conclusions and proposals for improving the source base and practice of lawmaking and law enforcement. On the basis of the method of comparative legal analysis, the development of the system of sources of law in general, sources of law of other countries and the Republic of Kazakhstan is investigated. Based on the method of historical research, the role and significance of historical sources in the development of the modern system of sources of law are revealed. The method of system analysis was used to study the definitions of sources of law existing in the theory of law. The author's vision on the correlation between the source and form of law is formulated. The properties and functions of sources of law are determined by the factors for the legal system, on the basis of which lawmaking and law enforcement activities are built. The methods of classification of sources of law are analyzed, the possibilities of using various grounds for the classification of sources of law are considered in order to systematize them and determine their potential in the process of law enforcement. The possibility of introducing the concept of «auxiliary» sources of law into the domestic theory of law, as it exists in the theory and practice of international law, has been investigated. The possibilities and basic patterns of integration of modern Romano-Germanic and Anglo-Saxon legal systems are considered. The conclusion about the existence of the tendency of «westernization» of the system of Kazakhstani law is formulated; the use of judicial precedent as a source of law in the context of a «special legal regime» on the territory of the MFC «Astana».